Do Puerto Rican Youth with Asthma and Obesity Have Higher Odds for Mental Health Disorders? - Acosta-Pérez, Edna (2012)
Island Puerto Rican (PR) youth experience disproportionately high asthma and obesity rates compared with other racial/ethnic groups on the U.S. mainland. Previous research has demonstrated associations of chronic disease with psychiatric disorders. We examined the relationship among anxiety/depressive disorders, asthma and obesity in an epidemiological community sample of youth. The sample (n=656) was derived from the second wave of an island-wide probabilistic representative household sample of PR youth stratified and based on whether or not they had a diagnosis of asthma and/or depressive/anxiety disorder. For this study we used the subpopulation ages 10–19 years. Asthma and obesity were significantly related to higher odds of depressive/anxiety disorders in youth. Obesity moderated the relationship between asthma attacks and depressive/anxiety disorders. The relationship between asthma attack and higher odds for depressive/anxiety disorders was only present in the non-obese group. Among the obese, females show a significant increase from 11–36% in the prevalence of anxiety/depressive disorders. Asthma and obesity were highly prevalent and a significant association was found between asthma attack and depressive/anxiety disorders. The effects of asthma and obesity were not additive; the prevalence for psychiatric disorder for those having both conditions did not increase above the prevalence associated having only one of the conditions. Future studies should consider including longitudinal designs and examine the extent to which important variables not included in this study such as body image dissatisfaction, particularly among females, teasing and discrimination may moderate the relationship between obesity and depressive and anxiety disorders in youth.